2006
DOI: 10.1007/s10286-006-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sympathetic cardiac modulation in bruxism patients

Abstract: Sleep bruxism, an oral parafunction including teeth clenching and grinding, might be related to increased stress. To evaluate sympathetic cardiac activity in bruxism patients, we monitored cardiac autonomic modulation using spectral analysis of heart rate variability and compared results to those of age-matched healthy volunteers. In bruxism patients, sympathetic cardiac activity was higher than in volunteers. The increased sympathetic tone suggests increased stress and might be related to occlusal disharmonie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
0
26
0
3
Order By: Relevance
“…Rugh et al reported that nocturnal EMG activity increased with stress (17). In addition, a study of 20 clinically diagnosed sleep bruxers and 20 healthy volunteers found that the sympathetic cardiac activity of the bruxers was higher than that of the non-bruxers, suggesting that the bruxers were affected by stress (18). On the contrary, in a study of 100 sleep bruxers performed over a 15 night recording period, Pierce et al found no association between bruxism and stress (23).…”
Section: The Changes In the Ten-division Vas Scoresmentioning
confidence: 99%
“…Rugh et al reported that nocturnal EMG activity increased with stress (17). In addition, a study of 20 clinically diagnosed sleep bruxers and 20 healthy volunteers found that the sympathetic cardiac activity of the bruxers was higher than that of the non-bruxers, suggesting that the bruxers were affected by stress (18). On the contrary, in a study of 100 sleep bruxers performed over a 15 night recording period, Pierce et al found no association between bruxism and stress (23).…”
Section: The Changes In the Ten-division Vas Scoresmentioning
confidence: 99%
“…Sleep bruxism, similar to the movement disorders previously discussed, appears to also result in augmented cardiac sympathetic activity [49,50]. This cardiac sympathetic activity can be suppressed in sleep with clonidine [51].…”
Section: Sleep Bruxismmentioning
confidence: 86%
“…Se ha relacionado un elevado tono simpático general durante la vigilia con individuos que presentan BS (17). Los episodios de AMMR/BS están asociados con el movimiento corporal y también con la excitación cortical (14,(18)(19)(20), más específicamente, se ha demostrado que una gran proporción de episodios AMMR/BS (87,3%) ocurren en la fase A del patrón cíclico alterno (CAP) (19).…”
Section: Tono Simpático Muscularunclassified